ANALISIS PERSIAPAN GURU MATEMATIKA PRA PEMBELAJARAN DI KELAS - Mila Karmila Sidik; Juraid Somalua (Universitas Muhammadiyah Semarang, 2020)
The purpose of this research is to describe the preparation of pre-learning math teachers in the classroom. This research uses a qualitative approach. The research period was conducted on June 16-23, 2020. The subjects of the study were teachers in east Lisabata sub-district of three teachers from each school, namely SMP N 5 Seram Utara Barat, SMP N 6 Seram Utara Barat Satu Atap, and SMA N 49 Maluku Tengah. The research procedure covers three stages, namely the preparation, implementation, and analysis of data. Data collection techniques are: observation, interview, documentation. Analyze the data in this study through steps: data reduction, data presentation and draw conclusions. The results of the study namely AS and SLK do not make a summary of the subject matter, KS and SLK, do not prepare the needs of other tools or learning resources in the delivery of subject matter, AS and SLK do not use media or props to be used in the learning process.